Fatigue Intensity in Cervical and Breast Cancer Survivors: Difference in Each Stage of Cancer Survivorship - Ni Putu Wulan Purnama Sari (National Cancer Center - Dharmais Cancer Hospital, 2019)
Background: Cervical and breast cancers are the two top leading cases of female cancer in Indonesia. Nowadays, many survivors with various degree of cancer-related fatigue (CRF) were found in the community context. This study aimed to compare and analyse the differences of CRF intensity in cervical cancer survivors (CCS) and breast cancer survivors (BCS) generally, and in each stage of cancer survivorship, specifically.Methods: This cross-sectional study involved 47 CCS and 55 BCS in the district of Rangkah, Gading, and Pacar Keling, Surabaya, Indonesia (n=102). Instrument of Fatigue Symptom Inventory (FSI) was used for data collection. Descriptive statistic, independent sample t-test, and one way ANOVA test were used for data analysis (α<.05).Results: Most respondents were short term survivors (43.14%) with mild CRF (66.67%) in both cases. Higher intensity of CRF was found in CCS compared to BCS. Worst CRF was found more in acute and short term survivorship in BCS compared to more in long term survivorship in CCS. There was no significant difference of CRF found between CCS and BCS (p=.63), and CRF was not significantly different between each stage of cancer survivorship in both cases (p=.883 and p=.117 for CCS and BCS respectively), but CRF intensity in the worst and lightest time possible was significantly different between CCS and BCS (p=.000).Conclusions: There was no significant difference of CRF between cases and stages of survivorship in CCS and BCS, but CRF intensity in the worst and lightest time possible was significantly different between those groups.